Topical ivermectin improves allergic skin inflammation. Issue 8 (6th February 2017) - Ventre, E.; Rozières, A.; Lenief, V.; Albert, F.; Rossio, P.; Laoubi, L.; Dombrowicz, D.; Staels, B.; Ulmann, L.; Julia, V.; Vial, E.; Jomard, A.; et al.
Abstract: Background: Ivermectin (IVM) is widely used in both human and veterinary medicine to treat parasitic infections. Recent reports have suggested that IVM could also have anti‐inflammatory properties. Methods: Here, we investigated the activity of IVM in a murine model of atopic dermatitis (AD) induced by repeated exposure to the allergen Dermatophagoides farinae, and in standard cellular immunological assays. Results: Our results show that topical IVM improved allergic skin inflammation by reducing the priming and activation of allergen‐specific T cells, as well as the production of inflammatory cytokines. While IVM had no major impact on the functions of dendritic cells in vivo and in vitro, IVM impaired T‐cell activation, proliferation, and cytokine production following polyclonal and antigen‐specific stimulation. Conclusion: Altogether, our results show that IVM is endowed with topical anti‐inflammatory properties that could have important applications for the treatment of T‐cell‐mediated skin inflammatory diseases.